Resolving taxonomic problems through cuticular analysis in Early Cretaceous bennettitalean leaves from Patagonia - Carrizo, Martin Alejandro; Lafuente Diaz, Maiten Amalia; del Fueyo, Georgina Marisa (Cretaceous Research)
The genus Ptilophyllum Morris is one of the most common bennettitalean leaf genera found in the Cretaceous megafloras from Western Gondwana, particularly Patagonia and Antarctica. Among several specimens, the similarity in the morphology of their leaves make them hard to distinguish from each other, which usually leads to misinterpretations. Therefore, the study of the epidermal features in this taxon is essential, especially because the occurrence of papillae, its size, forms, and distributions are relevant for the differentiation of species. Based on these considerations, the erection of a new Ptilophyllum species here indicated that the papillae are a key character to resolve taxonomic conflict between some of the Cretaceous taxa from Western Gondwana. Ptilophyllum eminelidarum sp. nov. Carrizo, Lafuente Diaz et Del Fueyo, was recovered from the Springhill Formation at the Río Correntoso and Estancia El Salitral localities, Santa Cruz province, Argentina. Epidermal foliar features are fully described with the aid of light and electron (SEM and TEM) microscopy. This new bennettitalean species is characterized by pinnate leaves with an epidermis bearing two distinct, uniformly distributed, papillae morphologies: the compound papillae are situated on the vein cells, and the small simple papillae are located between veins. The cuticular membrane ultrastructure consists of three layers corresponding to the cuticle proper (A2) with fibrillar aspect and the cuticular layers B1 and B2 with homogeneous-granular and fibrillar-granular aspect, respectively. This combination of features are unique to this species, differentiating it from other coetanean species of the genus from Western Gondwana. This finding complements and reinforces previous knowledge regarding the megaflora of the Springhill Formation and underscores the important role of the Bennettitales within the plant associations during the Cretaceous of Patagonia. Fil: Carrizo, Martin Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. ...